The future of library space - Hines, Samantha Schmehl; Moore Crowe, Kathryn (Advances in library administration and organization ;, 2017)
Libraries are dealing with unprecedented changes on several fronts: technological developments, funding difficulties, and an increasing need to prove themselves to a demanding population. These factors understandably impact physical library space. Looking toward the future, what changes can we expect to see in how libraries use space. This volume of Advances in Library Administration and Organization (ALAO) will focus on the future of library spaces. ALAO offers long-form research, comprehensive discussions of theoretical developments, and in-depth accounts of evidence-based practice library administration and organization. The series aims to answer the questions "How have libraries been managed and how should they be managed?" It goes beyond a platform for the sharing of research to provide a venue for dialogue across issues, in a way that traditional peer reviewed journals cannot. Through this series practitioners can glean new approaches in challenging times and collaborate on the exploration of scholarly solutions to professional quandaries.